2022
DOI: 10.31083/j.jomh1808161
|View full text |Cite
|
Sign up to set email alerts
|

De Novo or Increasing Lower Urinary Tract Symptoms during COVID-19 Infection: Long-term Results

Abstract: Background: How COVID-19 affects lower urinary tract symptoms (LUTS) in men has not been demonstrated by published research. This study examined the de novo development of LUTS and the change in the severity of pre-existing LUTS in men hospitalized with COVID-19. A follow-up period of 12 months after COVID-19 infection provided data on the long-term effect of COVID-19 vs. LUTS. Methods: Data were collected from 70 male patients diagnosed with COVID-19 via nasopharyngeal swab RT-PCR technology between June 2020… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Current literature only contains small-scale case series and observational studies investigating the clinical correlation between COVID-19 and male LUTS, albeit with interesting results. Five small-scale studies on male COVID-19 patients that included up to 356 subjects observed statistically significant increase of LUTS scores, such as the International Prostate Symptom Score (IPSS) or the National Institute of Health-Chronic Prostatitis Symptom Index (NIH-CPSI) after COVID-19 compared to that before COVID-19 [12][13][14][15][16]. Apart from symptom score, bladder diary data also demonstrated worsening LUTS in COVID-19 patients [15].…”
Section: Introductionmentioning
confidence: 99%
“…Current literature only contains small-scale case series and observational studies investigating the clinical correlation between COVID-19 and male LUTS, albeit with interesting results. Five small-scale studies on male COVID-19 patients that included up to 356 subjects observed statistically significant increase of LUTS scores, such as the International Prostate Symptom Score (IPSS) or the National Institute of Health-Chronic Prostatitis Symptom Index (NIH-CPSI) after COVID-19 compared to that before COVID-19 [12][13][14][15][16]. Apart from symptom score, bladder diary data also demonstrated worsening LUTS in COVID-19 patients [15].…”
Section: Introductionmentioning
confidence: 99%